2005
DOI: 10.1158/1078-0432.ccr-05-0548
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Immunohistochemical Expression of Ezrin in Highly Malignant Soft Tissue Sarcomas

Abstract: Purpose: Ezrin is a cytoskeleton linker protein that is actively involved in regulating the growth and metastatic capacity of cancer cells. It has recently been reported to be involved in dissemination of pediatric soft tissue sarcoma (STS). Experimental Design:To further evaluate the prognostic value of ezrin in STS progression, we screened 50 primary STSs of high malignancy grade using immunohistochemistry. At the initial surgery, all patients were without local or distant metastasis. The expression was then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
90
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(105 citation statements)
references
References 23 publications
13
90
0
2
Order By: Relevance
“…We observed that immunohistochemical detection of ezrin is not statistically associated with poor prognosis as reported for other cancer types, such as uveal malignant melanoma, 31 high-grade soft tissue tumors, 32 or recently found in osteosarcomas. 2 However, the patients with ezrin expression in primary tumors have a worse prognosis for survival.…”
Section: Discussionsupporting
confidence: 66%
“…We observed that immunohistochemical detection of ezrin is not statistically associated with poor prognosis as reported for other cancer types, such as uveal malignant melanoma, 31 high-grade soft tissue tumors, 32 or recently found in osteosarcomas. 2 However, the patients with ezrin expression in primary tumors have a worse prognosis for survival.…”
Section: Discussionsupporting
confidence: 66%
“…[17][18][19][20][21][22] Although this adverse prognostic effect has been established in human malignant neoplasms derived from both epithelial and mesenchymal origins, exceptions to this general rule were occasionally reported, suggesting that there may be cellspecific functions for ezrin in tumor progression. [17][18][19][20][21][22] For instance, the loss of ezrin expression in serous ovarian carcinomas was shown to be associated with poor survival. 34 Moreover, unlike osteosarcomas and adult high-grade sarcomas, ezrin overexpression was recently found not predictive of clinical outcomes in synovial sarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, this 38,39 Through the modulation of diverse actin-based functions, ezrin is known as a key component of the molecular chain connecting the metastasis-associated cell surface proteins with the signal transduction network. [17][18][19][20][21][22] What remain less clear for this pathogenetic role of ezrin are the crucial elements of its various downstream effectors, which may vary among different tumor types. In the murine model of rhabdomyosarcoma, the prometastatic activity of ezrin was recently substantiated to be mediated in part through the Rho family of small G proteins, consistent with the firmly established reciprocal relationship between the ERM proteins and Rho activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations